Nucleocapsid Protein (N) of Peste des petits ruminants Virus (PPRV) Interacts with Cellular Phosphatidylinositol-3-Kinase (PI3K) Complex-I and Induces Autophagy - Yash Chaudhary; Juhi Jain; Sharad Kumar Gaur; Prabhakar Tembhurne; Shanmugam Chandrasekar; Muthuchelvan Dhanavelu; Sharvan Sehrawat; Rajeev Kaul (Viruses, 2023)
Autophagy is an essential and highly conserved catabolic process in cells, which is important in the battle against intracellular pathogens. Viruses have evolved several ways to alter the host defense mechanisms. PPRV infection is known to modulate the components of a host cell’s defense system, resulting in enhanced autophagy. In this study, we demonstrate that the N protein of PPRV interacts with the core components of the class III phosphatidylinositol-3-kinase (PI3K) complex-I and results in the induction of autophagy in the host cell over, thereby expressing this viral protein. Our data shows the interaction between PPRV-N protein and different core components of the autophagy pathway, i.e., VPS34, VPS15, BECN1 and ATG14L. The PPRV-N protein can specifically interact with VPS34 of the PI3K complex-I and colocalize with the proteins of PI3K complex-I in the same sub-cellular compartment, that is, in the cytoplasm. These interactions do not affect the intracellular localization of the different host proteins. The autophagy-related genes were transcriptionally modulated in PPRV-N-expressing cells. The expression of LC3B and SQSTM1/p62 was also modulated in PPRV-N-expressing cells, indicating the induction of autophagic activity. The formation of typical autophagosomes with double membranes was visualized by transmission electron microscopy in PPRV-N-expressing cells. Taken together, our findings provide evidence for the critical role of the N protein of the PPR virus in the induction of autophagy, which is likely to be mediated by PI3K complex-I of the host.